2011
DOI: 10.3109/02770903.2011.558152
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Age and Birth Cohort with Total and Specific IgE Antibody Levels

Abstract: The associations of total and specific IgE levels with age and birth cohort were different. Thus, in comparing the results of IgE antibody testing done in different years, even for patients of the same age, the possibility of a birth cohort effect on IgE levels should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
2
1
Order By: Relevance
“…Age‐related alterations in the serum IgE levels have been the subject of disagreement. While most of the previous studies demonstrate a decrease in the levels of IgE in elderly both in allergic and healthy individuals, others do not indicate a significant change . We found that Indians showed a negative correlation between age and IgE levels (for Dermatophagoides ), while the correlations in other races was insignificant.…”
Section: Discussioncontrasting
confidence: 63%
“…Age‐related alterations in the serum IgE levels have been the subject of disagreement. While most of the previous studies demonstrate a decrease in the levels of IgE in elderly both in allergic and healthy individuals, others do not indicate a significant change . We found that Indians showed a negative correlation between age and IgE levels (for Dermatophagoides ), while the correlations in other races was insignificant.…”
Section: Discussioncontrasting
confidence: 63%
“…Perzanowski and colleagues (2016) showed that children diagnosed with asthma after the age of 12 tended to be less sensitized to mammalian dog dander and had lower IgE levels than children diagnosed before the age of 12 31 . Considering the increasing prevalence of dog ownership over time, a cohort effect could contribute to this difference 47 . Therefore, age might also play a key role in the sensitization profiles of dog allergen components.…”
Section: Discussionmentioning
confidence: 99%
“… 31 Considering the increasing prevalence of dog ownership over time, a cohort effect could contribute to this difference. 47 Therefore, age might also play a key role in the sensitization profiles of dog allergen components.…”
Section: Discussionmentioning
confidence: 99%